PREMOGAWA SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATERI KEKONGRUENAN DAN KESEBANGUNAN SISWA MTsN 2 PONOROGO - HEFIN DWI RIVIA JULIANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The purpose of this study was to improve learning outcomes of mathematics on the subject of congruence and similarity in class IX H MTsN 2 Ponorogo in the academic year 2021/2022. This research method is best practice research. The research subjects were students of MTsN 2 Ponorogo class IX H in the 2021/2022 academic year. The learning approach used is Problem Based Learning, with the learning model used is